Diagnóstico e avaliação das áreas de destino final dos resíduos sólidos urbanos no estado do rio grande do norte - Brito, Acácio Sânzio de (2009)
This work aims to present the diagnosis and the evaluation of areas of final destination of urban solid waste in Rio Grande do Norte (RN) state. The survey was based on the experience of the State of São Paulo, which made its first inventory in 1997, through its Companhia de Tecnologia de Saneamento Ambiental CETESB. The methodology for the structuring of diagnosis was the Índice de Qualidade de Aterros de Resíduo -- IQR, developed by the Institute for Technological Research of São Paulo (ITRP). The calculation is based on the completion of a matrix that contains information about the main features of the site, infrastructure and operating conditions of the area of waste disposal. This study intends to subsidize the state government of Rio Grande do Norte through its State Secretariat of Environment and Water Resources and the Instituto de Desenvolvimento Sustentável e Meio Ambiente do RN (IDEMA), as well as federal, state and municipal authorities, in the definition of public policies for integrated management of municipal solid wastes to take account of environmental preservation and improvement of sanitary conditions of Natal-RN population.